Deciphering the connection: Exploring the relationship between finance, trade, and urbanization in the ecological fabric of African economies - Kingsley I. Okere; Ismail O. Fasanya (Sustainable Environment)
This study contributes to the Sustainable Development Goal 15 by examining the dynamics of balancing the ecological footprint and meeting fundamental human needs in terms of food and shelter. The analysis utilizes a panel dataset comprising 9 countries with ecological deficits, covering the period from 1971 to 2022. The estimators employed in the study are robust to cross-sectional dependence and allow for heterogeneous slope coefficients. The findings, based on the FE-DK and MMQR models, provide empirical evidence supporting the ecological deficit hypothesis. The validity of the ecological deficit hypothesis is verified by the inverted U-shaped nexus between economic growth and ecological deficits. Finance plays a mitigating role in reducing the ecological deficit for food, but it is associated with higher levels of deficit for shelter, particularly at the upper quantile. Trade openness exacerbates the ecological deficit for food, but it helps reduce the deficit for shelter. Robustness analysis, conducted using the half-panel jackknife multivariate Wald-type test, confirms that the covariates exhibit Granger-causal relationships with the ecological deficit. Bidirectional causal relationships are observed between the ecological deficit for food and squared economic growth. Additionally, bidirectional relationships exist between trade and urban population and the ecological footprint for shelter. The findings offer useful insights for policymakers and stakeholders that are working towards achieving sustainable development.